Atypical Familial Mediterranean Fever in a Japanese Boy with Heterozygous MEFV p.Ser503Cys Exon 5 Variant - Tomonobu Sato; Shunichiro Takezaki; Takeru Goto; Shinichi Ishikawa; Kazumi Oura; Asuka Takahata; Haruki Shiraishi; Yuji Maruo; Norio Sato; Takashi Suganuma; Makoto Mikawa (Hindawi Limited, 2021)
Periodic fever syndromes are heterogeneous diseases. Familial Mediterranean fever (FMF) is one of the hereditary periodic fever diseases caused by a Mediterranean fever (MEFV) gene abnormality. FMF can be categorized as typical or atypical, based on clinical findings and genetic screening. Atypical FMF has a wide variation of clinical findings and disease-causing mutations of MEFV. Therefore, it is sometimes difficult to diagnose an unknown fever as FMF. To date, a large number of various typical and atypical FMF cases have been reported in Japan. Here, we describe a Japanese boy with heterozygous MEFV p.Ser503Cys exon 5 variant who developed periodic fever. He was treated with colchicine; a complete eradication of his fever and various accompanying symptoms have been subsequently achieved for more than a year. Given that there have been a few reports about patients with this variant, little is known about the genetic and phenotypic role of heterozygous MEFV p.Ser503Cys exon 5 variant. It is therefore imperative to consider atypical FMF as a differential diagnosis when a periodic fever is encountered. Furthermore, we suggest that it is worthwhile to integrate MEFV gene analysis with the potential effects of colchicine treatment in patients with periodic fever.